2020
DOI: 10.1016/j.heliyon.2020.e05082
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' aggressive behaviors: what is considered acceptable and why?

Abstract: Despite numerous criticisms of teachers' aggressive behaviors, there has been no consensus on which specific behaviors are considered unacceptable. Some legal regulations on this topic are perceived as unclear or are not enforced, which can lead to disputes between parents and teachers. This study investigated the acceptance of teachers' aggressive behaviors. The participants were 203 teachers and 293 parents of middle and high school students. The results are as follows: (1) parents and teachers tend to have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…The results showed that this type of behavior can lead to decreased participation, decreased interest in classroom activities, loss of self-confidence, and decreased academic motivation. These findings are consistent with previous studies, such as the one conducted by Kerig et al (2012) who found that aggressive teacher behavior can discourage academic motivation in students, as well as the findings of Surganingrat et al (2020) who emphasized that aggressive teacher behavior can result in students withdrawing from participation in the classroom. Also, the null hypothesis indicated the presence of a significant disparity between the aggressive behavior exhibited by male and female teachers.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results showed that this type of behavior can lead to decreased participation, decreased interest in classroom activities, loss of self-confidence, and decreased academic motivation. These findings are consistent with previous studies, such as the one conducted by Kerig et al (2012) who found that aggressive teacher behavior can discourage academic motivation in students, as well as the findings of Surganingrat et al (2020) who emphasized that aggressive teacher behavior can result in students withdrawing from participation in the classroom. Also, the null hypothesis indicated the presence of a significant disparity between the aggressive behavior exhibited by male and female teachers.…”
Section: Discussionsupporting
confidence: 93%
“…However, according to Usher and Morris (2012), one's motivation for schoolwork can be either intrinsic (coming from inside oneself) or extrinsic (motivated by outside forces).They also pointed out that various factors, such as the behavior and words of teachers, can either enhance or diminish a student's academic motivation. This idea was reinforced by the findings of Surganingrat et al (2020), who discovered that teacher's verbal aggression can have negative consequences on students, such as increased aggression and withdrawal from class participation, and concluded that verbal aggression can be even more damaging than physical aggression, with long-lasting effects on learners.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research of Suryaningrat, Mangunsong, and Riantoputra (2020), while focusing on disputes between teachers and parents, offers interesting points of comparison with our topic.…”
Section: Limits and Discussionmentioning
confidence: 99%
“…Teachers considered lower average violence than students because they reported less violence and believed that students punishment was so useful for them to act better ( Cluver et al, 2018 ), even those who experienced violence behaved more aggressively ( Scharpf et al, 2021 ). Suryaningrat et al (2020) found that aggressive behavior had a direct relationship with aging ( Suryaningrat et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%